Formulation of Poloxamers for Drug Delivery - Bodratti, Andrew M. (J Funct Biomater, 2018)
Poloxamers, also known as Pluronics(®), are block copolymers of poly(ethylene oxide) (PEO) and poly(propylene oxide) (PPO), which have an amphiphilic character and useful association and adsorption properties emanating from this. Poloxamers find use in many applications that require solubilization or stabilization of compounds and also have notable physiological properties, including low toxicity. Accordingly, poloxamers serve well as excipients for pharmaceuticals. Current challenges facing nanomedicine revolve around the transport of typically water-insoluble drugs throughout the body, followed by targeted delivery. Judicious design of drug delivery systems leads to improved bioavailability, patient compliance and therapeutic outcomes. The rich phase behavior (micelles, hydrogels, lyotropic liquid crystals, etc.) of poloxamers makes them amenable to multiple types of processing and various product forms. In this review, we first present the general solution behavior of poloxamers, focusing on their self-assembly properties. This is followed by a discussion of how the self-assembly properties of poloxamers can be leveraged to encapsulate drugs using an array of processing techniques including direct solubilization, solvent displacement methods, emulsification and preparation of kinetically-frozen nanoparticles. Finally, we conclude with a summary and perspective.